Effect of curing Helicobacter pylori infection on intragastric acidity during treatment with ranitidine in patients with duodenal ulcer. Issue 1 (July 1997) - Labenz, J; Tillenburg, B; Peitz, U; Verdú, E; Stolte, M; Börsch, G; Blum, A L
Abstract : BACKGROUND: In patients with duodenal ulcer cure of Helicobacter pylori infection resulted in a pronounced decrease in intragastric pH during treatment with omeprazole. AIM: To test the hypothesis that treatment of H pylori adversely affects the pH response to ranitidine. PATIENTS: Eighteen patients with duodenal ulcer who were infected with H pylori were studied. METHODS: Twenty four hour pH recordings were performed during treatment with ranitidine (300 mg) at night before and four to six weeks after cure of H pylori infection. Presence of H pylori was assessed by a rapid urease test, culture, histology, and a 13C urea breath test. Also, the fasting gastrin concentrations were measured before and after treatment for H pylori infection. RESULTS: Cure of H pylori infection resulted in a considerable improvement in both antral and corpus gastritis and a decrease in fasting gastrin concentrations. As a result of the cure the night time intragastric pH during treatment with ranitidine decreased (median pH 6.8 v 5.4; p = 0.007), whereas the acidity during the daytime was not affected. CONCLUSIONS: In patients with duodenal ulcer the intragastric pH during treatment with ranitidine depends on H pylori. However, the loss of effectiveness in altering pH seems to be less pronounced than previously found with omeprazole.